Finance and development in West Africa - Cox-George, N. A. (D. Dobson, 1961)
The main focus of attention here is on the cyclical problems of financing development in the economy based on recent historical experience
Bibliography: p. 317-321.
osc 21/11/2018
Loans
Keywords: Finance, Public; Sierra Leone